Ophthalmic Microemulsion: A Comprehensive Review - KALE MOHAN,; SURUSE PRAVIN,; BODHAKE ATUL, (International Journal of Pharma and Bio Sciences, 2012)
The design and development of new drug delivery systems with the intention of enhancing the efficacy of existing drugs is an ongoing process in pharmaceutical research. It is necessary for a pharmaceutical solution to contain a therapeutic dose of the drug in a volume convenient for administration. In last decade, o/w micro/lipid emulsions have been recognized as an interesting and promising ocular topical delivery vehicle for lipophilic drugs. The aim of present review is to present the potential of o/w and lipidmicroemulsions for ocular delivery of lipophilic drugs. The review covers an update on the state of the art of incorporating the lipophilic drugs, a brief description concerning the components and the classification of lipid/oil in water emulsions. The ocular metabolism after topical instillation and the applications of micro/lipid emulsions are thoroughly discussed.